The Effect of Volunteer Motivation and Servant Leadership on Organizational Commitment at AIESEC Members of Universitas Muhammadiyah Malang - Dewi Fajar Sari; Nurul Asfiah; Sandra Irawati (Universitas Muhammadiyah Malang, 2022)
AIESEC UMM is a non-profit organization based at the University of Muhammadiyah Malang. This organization was established as a platform for young people to develop their leadership through practical experience. The aims of this research are: (1) how volunteer motivation, servant leadership, and organizational commitment of AIESEC UMM members, (2) to analyze the effect of volunteer motivation on organizational commitment of AIESEC UMM members, (3) to analyze the effect of servant leadership on organizational commitment of AIESEC UMM members. The population and sample in this study were all members of AIESEC UMM 2021, totaling 70 people. The analysis technique used in this research is multiple linear regression analysis. The results of this study indicate that (1) the volunteer motivation of AIESEC UMM members is in the high category, servant leadership in the AIESEC UMM organization is implemented well, and the organizational commitment of AIESEC UMM members is also in the high category, (2) volunteer motivation has a positive and significant effect on organizational commitment of AIESEC UMM members, (3) servant leadership has a positive and significant effect on organizational commitment of AIESEC UMM members